Utilizing collaborative writing strategy to create skills of 21st century: EFL learners’ perceptions - M. Fadhly Farhy Abbas; Vina Fathira (STAI Hubbulwathan Duri, 2022)
Utilizing collaborative writing strategy in a writing class seems very helpful and beneficial. Through collaborative writing, it can build up critical thinking, creativity, communication, and collaboration as the skills of 21st century of learners in the learning process. The purpose of this research is to investigate English as a foreign language (EFL) learners’ perceptions toward the use of collaborative writing strategy in a writing class. The research method employed was qualitative method with descriptive research design. 51 EFL learners were involved in this research as respondents of this research. The data was collected through questionnaire with 20 statements available underlying four general perceptions so called: perceptions of academic writing concept, perceptions of cooperation, perception of writing skills, and perceptions of learning atmosphere. The data from questionnaire was analyzed descriptively. The findings showed that EFL learners’ perceptions on the implementation of collaborative writing strategy in a writing class was positive. EFL learners’ response towards questionnaire were dominated by response “agree” and “strongly agree”. From this findings, it can be concluded that EFL learners’ perceptions on the application of collaborative writing strategy in a writing class are varied. It is recommends the skills of 21st century can be build up through the implementation of collaborative writing strategy in a writing class.